Pengembangan LKPD Berbasis Model Pembelajaran AIR Berorientasi Pada Peningkatkan Kemampuan Komunikasi Matematika - Atika Nur Hidayati; Alben Ambarita; Dwi Yulianti (Jurnal Inovasi Matematika, 2021)
From the results of the answers to the test of mathematical communication skills and the deployment of the questionnaire obtained the problem, namely the low capacity of mathematical communication students, the difficulty of students to write the form of mathematical symbols, and the limitations of teaching materials used during learning in class V in elementary school. This study aimed to develop valid worksheets of students (LKPD) on building simple spaces in class V elementary school, knowing the practicality of LKPDs from users, educators and students, and knowing the effectiveness of LKPD on increasing mathematical communication skills. The method of development used in this study referred to the research design of Borg and Gall. Data collection techniques were carried out through documentation, observation, questionnaires, and students' mathematical communication skills tests. The subjects of this study were 25 control class students and 25 experimental class students at SDN 1 Semuli. The study results stated that LKPD products based on the AIR learning model were valid, practical, and effective in improving students' mathematical communication skills. It was proven by material experts, media experts, and language experts validating results with the "Very Valid" category. LKPD based on AIR learning models was practiced to be used by fulfilling the aspects of attractiveness, convenience, and usefulness with the "very practical" category. LKPD-based AIR learning models were effectively used to improve students' mathematical communication skills in the pretest and post-test scores, with the results of the calculation of the experimental class n-gain entry in the category was quite effective